Association between Metabolic Syndrome Score and Subclinical Atherosclerosis - Ming Yi; Xinyi Wang; Yan Li; Xuewen Li; Jin Si; Yinghua Zhang; Keling Xiao; Lijie Sun; Haoyu Zhang; Jinghao Sun; Zhaoli Liu; Jiaying Lin; et al. (Reviews in Cardiovascular Medicine)
Background: Previous studies have presented conflicting results on the correlation between metabolic syndrome (MetS) and subclinical atherosclerosis. However, the binary MetS definition cannot reflect the severity of metabolic disorders continuously and dynamically. The present study calculated the MetS score and explored the association between MetS score and subclinical atherosclerosis. Methods: A total of 840 participants were included in this observational, cross-sectional study; 66.55% of participants were men, and the median age was 61.00 years (53.00, 67.00). Brachial–ankle pulse wave velocity (baPWV) and brachial flow-mediated dilation (bFMD) values were measured from October 2016 to January 2020. Spearman’s correlation and multiple linear regression analyses were conducted to explore the correlation between the MetS score and baPWV and bFMD. Arterial stiffness was defined as baPWV ≥1400 cm/s, while endothelial dysfunction was described as bFMD >6%. Multiple logistic regression was performed to explore the effects of MetS and MetS score on arterial stiffness and endothelial dysfunction. Results: The MetS score was significantly associated with baPWV (β = 73.59, 95% CI (42.70, 104.48); p < 0.001) and bFMD (β = –0.43, 95% CI (–0.75, –0.10); p = 0.010) after adjusting for covariates. Compared with the binary definition of MetS, the MetS score was a more significant predictor for arterial stiffness (odds ratio, OR = 2.63, 95% CI (1.85, 3.74); p < 0.001) and endothelial dysfunction (OR = 1.33, 95% CI (1.01, 1.76); p = 0.040). Leukocyte count (r = 0.32; p < 0.001) and high-sensitivity C-reactive protein (hs-CRP) (r = 0.17; p < 0.001) values were related to the MetS score. Conclusions: The MetS score is a clinically accessible assessment of metabolic status that can identify individuals at higher risk of subclinical atherosclerosis.